Analysis of a Factors Affecting Use of Accounting Information in Small and Medium Businesses (MSMEs) on Medan City - Fidar Putri Waruwu; Puja Rizqy; Oktarini Khamilah (Britain International for Academic Research (BIAR) Publisher, 2022)
Small and Medium Enterprises (SME) are types of businesses that can be directly managed by communities or families, small and medium-sized businesses have a big impact on a country's economy, one of which is reducing unemployment. So SMEs must continue to grow from time to time, this is one of the most important things An important factor for SMEs to develop their businesses is accounting information (financial reports). This research is a descriptive study of small and medium enterprises in the city of Medan. Cooperation department. This study aims to describe the characteristics of SMEs, and as an understanding and trend of accounting, applications use but also provides an overview of SME from a demographic perspective. Research results according to the report, by gender, the majority of SME entrepreneurs are women. Leading the ethnic groups are Javanese and Batak. Most of the business fields carried out are trading business. Most SME entrepreneurs have recorded their business activities, but still in a very simple form. How many people run the accounting process that communicates the final results? accounting information, namely financial statements. SME follow and understand accounting training materials are provided by the cooperative.